Clinical impact of broad- versus narrow-spectrum empiric therapy in acute cholangitis: A Japanese claims database study - Kazuhiro Aoto; Ryo Inose; Yuichi Muraki (PLoS ONE, 2026)
The clinical benefit of broad-spectrum empiric therapy in patients with acute cholangitis is unclear. We aimed to evaluate the impact of broad-spectrum and narrow-spectrum empiric therapies on patient outcomes using a Japanese claims database. The study included patients who were diagnosed with acute cholangitis between April 2014 and August 2022, aged 18–99 years, received antibiotics, had blood cultures collected, and underwent biliary drainage. Patients who received empiric therapy with carbapenems, piperacillin/tazobactam, or fourth-generation cephalosporins were included in the broad-spectrum group, whereas others were included in the narrow-spectrum group. Of the 4,755 eligible patients, 3,377 were categorized into the narrow-spectrum group and 1,378 into the broad-spectrum group. In the multivariate logistic regression analysis, older age, higher Charlson Comorbidity Index, the presence of sepsis, and intensive care unit admission were associated with increased 30-day in-hospital mortality, whereas the receipt of broad-spectrum empiric therapy was not (adjusted odds ratio, 1.37 [95% confidence interval CI, 0.84–2.23]). In the propensity score matching analysis, there was also no association between the receipt of broad-spectrum empiric therapy and 30-day in-hospital mortality (odds ratio, 1.43 [95% CI, 0.82–2.50]). Furthermore, in the propensity score-matched cohort, the broad-spectrum group had longer duration of intravenous antibiotic therapy (median interquartile range [IQR]: 8 [6 –11] day vs. 9 [7 –13] day; difference 1 day [95% CI, 0.31–1.69 day]) and length of hospital stay (median [IQR]: 13 [9 –20] day vs. 16 [11 –25] day; difference 3 day [95% CI, 1.87–4.13 day]), compared with the narrow-spectrum group. In this large-scale study using a Japanese claims database, broad-spectrum empiric therapy was not associated with improved clinical outcomes, compared with narrow-spectrum empiric therapy. Therefore, the necessity of broad-spectrum empiric therapy may be limited in clinical practice, and narrow-spectrum empiric therapy may represent an effective treatment strategy for acute cholangitis.